Case Report: Compound heterozygous variants in BHLHA9 cause complex syndactyly with oligodactyly, renal artery variation, and facial scar - Wei, Weidong; Wang, Xiaosha; Zhang, Tao; Zhong, Yongxing; Zhang, Jintang; Yuan, Hua; Shi, Xiaoliang; He, Yao; Pan, Haitao; Yang, Zhen; Wang, Yuejuan (Frontiers in Pediatrics, 2025)
BackgroundThe BHLHA9 gene, a member of the basic helix-loop-helix (bHLH) family of transcription factors, plays a critical role in limb development. Mutations in BHLHA9 have been associated with various limb malformations, including syndactyly and split-hand/foot malformation. This study aimed to identify and characterize novel BHLHA9 variants in a fetus with complex limb and renal abnormalities, providing further insights into the genetic basis of developmental disorders.MethodsWe performed Exome sequencing (ES) on a fetus with severe limb malformations and renal anomalies, along with the parents. Sanger sequencing was used to validate the identified variants. Evolutionary conservation analysis and structural predictions using AlphaFold were conducted to assess the functional impact of the variants. Protein-protein interaction networks were generated using the STRING database to explore potential functional partners of BHLHA9.ResultsThe proband exhibited multicystic dysplasia of the left kidney, an accessory renal artery, bilateral hand anomalies (four fingers with absent thumbs), bilateral foot syndactyly, and a facial scar. ES identified two novel compound heterozygous variants in the BHLHA9 gene: c.251C>T (p.Ala84Val) inherited from the father, and c.250_261dup (p.Ala84_Ala87dup) inherited from the mother. The two variants all located within the helix-loop-helix (HLH) domain, a critical region for protein-protein interactions and DNA binding. Evolutionary conservation analysis revealed that the affected residues are highly conserved across species, and structural predictions suggested that the two variants may disrupt the HLH domain's structural integrity. Protein-protein interaction analysis identified several potential functional partners of BHLHA9, including ASCL5, YWHAE, and PAFAH1B1, which are involved in transcriptional regulation, signaling pathways, and neuronal migration, respectively.ConclusionsThis study identifies novel compound heterozygous variants in the BHLHA9 gene represents a rare autosomal recessive disorder with severe limb and renal abnormalities. The c.251C>T and c.250_261dup variants, located within the HLH domain, is predicted to impair protein function, potentially disrupting limb development. These findings expand the spectrum of BHLHA9 mutations linked to developmental disorders and highlight the importance of the HLH domain in BHLHA9's regulatory role.